Development and validation of knowledge, perception and practice questionnaire on respiratory tract infection protective measures among Malaysian HAJJ PILGRIMS 2012 - Hanapi, Nur Sulwana Mohamad (2013)
Respiratory tract infection is a common infection among pilgrims during Hajj pilgrimage. A survey may provide information in preventing highly potential infections during Hajj pilgrimage. To validate a newly developed knowledge, perception and practice (KPP) questionnaire on respiratory tract infection protective measures among Malaysian Hajj pilgrims. After a detailed content and face validity evaluation, a self-administered questionnaire with 74 items was developed which assessed level of KPP towards respiratory tract infection protective measures. Data was collected from 303 pilgrims in 2012. Exploratory factor analysis (EFA) as data reduction for knowledge and perception domains was done using IBM SPSS 20.0. Further construct validity was evaluated on perception domain by Confirmatory Factor Analysis (CFA) using AMOS 18.0. All three domains including practice were checked for internal consistency. The mean (SD) of age of the respondents was 55.27 (10.32) years old. Majority of them were Malay (98.0%) and there were a total of 184 of male and 119 female Hajj pilgrims. Most of them were already married (87.8%). Only 76 respondents were worked with government and the highest level of education background was from secondary school (41.3%). There were three components extracted for each knowledge and perception domains in EFA. The perception domain performed model fit since fitness indeces were satisfactory in CFA as Chisquare(df),p-value= 17.62(11), 0.091; AIC=51.62; ECVI=0.256; TLI/CFI= 0.977/0.988; RMSEA=0.055; SRMR=0.04; Chisquare/(df)=1.60. Internal consistency (Cronbach’s alpha) for KPP were 0.51, 0.78 and 0.78, respectively. However, the CFA for knowledge domain was not performed due to unidentified problem of the model. Otherwise, it was considered content validated under a single construct. A total of thirty-six items were retained in the final questionnaire. The KPP was valid but less reliable only on knowledge domain. Thus, further, improvement should be performed to increase the validity and reliability of questionnaire.